Processo educacional e cultural dos Índios Ticuna: estudo do impacto sociopolítico causado pela Tríplice Fronteira - Brasil, Colômbia e Peru - Oliveira, Samuel Rocha de (2022)
The theme chosen for this research is the Educational and Cultural Process of the Ticuna Indians: study of the sociopolitical impact caused by the triple border – Brazil, Colombia and Peru. The research seeks to identify how the sociopolitical impact, caused by cultural diversity and experienced by the school community in the triple border, in the region of Alto Rio Solimões, influence the educational and cultural actions and procedures of the Ticuna Indians? The hypothesis of this research is that in recent years there have been significant changes in indigenous education in Ticuna villages in the region of the triple border, and currently indigenous people live with what survives of their culture, evidencing the originality of the research with the incessant struggle of the Ticuna to of the school to keep alive in their memories and daily practices the cultural legacy that still exists. To this end, we propose three objectives, namely: (i) approach the importance of the historical context of the Alto Rio Solimões region for the formation and cultural education of indigenous people; (ii) identify how the sociopolitical impact experienced by indigenous communities on the triple border of Brazil, Colombia and Peru, in the Alto Rio Solimões region, influences the educational process of the Ticuna; and (iii) to analyze whether the indigenous educational policy, as it is expressed, contributes to the Ticuna cultural transfer. The corpus selected for this research is the Ticuna people on the triple border in the Alto Rio Solimões region and the impact caused to indigenous Ticuna school education over the years. What justifies this research is the need to present how the Ticuna incorporate and assimilate existing multicultural aspects on the border in order to guarantee the continuity of everyday life in the villages through an intense system of exchanges with non-Indians. The theoretical framework that supports this work is anthropological research in the area of human sciences carried out by Castro (2002), Martins (2009), Nimuendajú (1977) and Oliveira Filho (1988), research related to indigenous school education such as Luciano ( 2006), Melià (1979), Monte (2000) and Oliveira (2012), among other authors that will be part of the scope of this work. This is a bibliographic research, supported by Gil's (2002, p. 45) thought, which can “allow the researcher to cover a much broader range of phenomena than he could directly research”. At the same time, we resorted to documental research, which according to Guba & Lincoln (1981) stands out for the fact that documents constitute a stable and rich source from which the researcher can extract evidence that supports his claims and allows the researcher greater accessibility. Documentary research also assists in the ratification, validation or complementation of information obtained by other data collection techniques. According to Cellard (2008) Document Analysis uses specific techniques for the apprehension and understanding of various types of documents and adopts a cautious process of selection, collection, analysis and interpretation of data. We understand that the facilities of the western world are tempting for the Ticuna, but the cultural elements that are part of their oral tradition can be reinforced in the pedagogical practice in indigenous school education. The Ticuna culture in our perception is a legacy for humanity. This research allowed reflections that help us to understand that the preservation of the culture of the Ticuna people nowadays goes through the school, in this sense this research can help in the search for ways that allow at the same time a natural opening to the facilities provided by the diversity of the frontier and the maintenance of the Ticuna culture, we hope that the material developed in this research can serve as a possible source of research and assistance for indigenous and non-indigenous teachers in the development of their educational practices.(AU)